Preoperative liraglutide modulates control of fat and glucose metabolism during cardiopulmonary bypass surgery - Robert van Wilpe; Abraham H Hulst; Steven E Thiessen; J Hans DeVries; Benedikt Preckel; Jeroen Hermanides (Endocrine Connections)
Introduction: Glucagon-like peptide-1 receptor agonists reduce insulin requirements and improve glucose control when administered before cardiac surgery. An increase in endogenous insulin release is the most likely mechanism, but this has never been studied in the setting of cardiac surgery. We hypothesized that liraglutide increases pancreatic insulin secretion during cardiac surgery with cardiopulmonary bypass (CPB). Methods: We performed a planned prospective substudy of a multicenter randomized-controlled trial (GLOBE trial, NTR6323). Patients undergoing cardiac surgery with CPB were randomized to receive either two preoperative subcutaneous injections of liraglutide or a matching placebo. We measured hormone concentrations before and after surgery, including insulin, glucagon, C-peptide and free fatty acid (FFA), and calculated HOMA-B, HOMA-IR and insulin/glucagon ratios. We compared between-group and before and after surgery differences in outcomes. Results: Metabolic hormone concentrations were measured in 37 participants. HOMA-B revealed that liraglutide increased insulin secretion relative to glycemia (258 ± 179 vs 116 ± 180, difference (95% CI): 142 (24–261), P = 0.004). While insulin, C-peptide and glucagon levels did not differ significantly between groups, the insulin/glucagon ratios were significantly higher in the liraglutide group (preoperatively: 1.09 ± 0.45 vs 0.79 ± 0.35 difference (95% CI): −0.30 (−0.57 to −0.03), P = 0.039). Overall, postoperative insulin levels decreased >60% from preoperative insulin levels (55 ± 31 to 21 ± 9.8, difference (95% CI): −29 (−36 to −22), P < 0.001). Conclusion: Preoperative liraglutide administration increased beta-cell function, measured as HOMA-B, and higher insulin/glucagon ratios. These results could explain the lower glucose and FFA concentrations in the liraglutide-treated patients. Interestingly, in both groups, we observed a remarkable drop in insulin and other hormone levels over the course of surgery.